Navigating Cultural Desolation: Exploring T.S. Eliot's Depiction of Anxiety and Fragmentation in The Waste Land - Mohammed Sarwar Alam; Hayati Binti Ismail (Secholian Publication, 2024)
Malaysian Journal of Social Sciences and Humanities (MJSSH) Volume: 8 No: 9 (page: 1-14)